PENGENALAN ALAT PORTABLE DIGITAL DAN PELATIHAN PENGUKURAN TINGGI BADAN PADA PETUGAS GIZI DAN KADER - Yanuarti Petrika; Sopiyandi; Rezza Dewintha (Poltekkes Kemenkes Bandung, 2022)
Stunting is a problem of poor nutrition based on height for age (TB/U) suffered from childhood and is an indicator of chronic malnutrition. Determination of stunting toddlers generally begins with taking anthropometric measurements in the form of toddler height. The aim of the community service is to increase knowledge of measuring height after being given training twice and to improve skills in measuring height with microtois. Community service is carried out at the Telaga Biru Health Center with the target of cadres and nutrition officers with a total of 18 respondents. Community service is carried out from May to July 2022. Training is given 2 times and evaluation monitoring is 1 time. The results of the training were seen from the knowledge of height measurement and height measurement skills. The data were analyzed by using the dependent test if the data was normally distributed and the Wilcoxon rank test if it was not normally distributed. The results of this community service show that there is a difference in knowledge of height measurement between the first and second training (p = 0.002). Respondents took more measurements in order (88.9%). In addition, 55.6% of respondents have done all stages of height measurement. It is necessary to refresh cadres by involving nutrition lecturers as companions every 3 months, especially in terms of measuring toddlers' height.